Analisis Data Berat Badan Dan Panjang Bayi Dengan Alat Ukur Panjang Dan Berat Badan Bayi Berbasi Arduino - Wahyudi, Bayu; Adella, Deny Julian; Nuha ABA, Muhammad Ulin (Elektrika, 2021)
Monitoring the nutritional status of infants at this time is mostly still using the manual method, by looking at anthropomeric standard books so that nutritional monitoring takes longer and is less practical. Babies need nutritional status based on age, weight, length of the baby (baby's height), and sex of the baby. To find out the nutritional condition of the baby, the author wants to develop a measurement tool for weight and length of the baby with the output data in Microsoft Excel. This study aims to design a baby's weight and length measurement tools with data output at Microsoft Excel and perform a function test. The process of detection in infants using ultrasonic sensors that serves to determine the height or length of the baby's body and load cell sensors to determine the baby's weight, then the LCD (Liquid Crystal Display) which displays the results of ultrasonic sensors and load cell sensors and Arduino Uno. The results of this study are an infant weight and height measurement tool with an arduino uno-based anthropometric index method with 2 ultrasonic sensors as height and length counters, and 1 load cell sensor as a weight calculator for infants that will later be displayed on the LCD screen.